1998
DOI: 10.1007/pl00005295
|View full text |Cite
|
Sign up to set email alerts
|

Brain histamine H3 receptors in rats with portacaval anastomosis: in vitro and in vivo studies

Abstract: The long-term effects of portacaval anastomosis (PCA) on histamine H3 receptors in rat brain were studied by in vitro and in vivo methods. The overflow of histamine from the anterior hypothalamus and from cortex after long-term PCA was determined by in vivo microdialysis. The binding properties of [3H]-R-alpha-methylhistamine in membranes from cortex, cerebellum, and rest of brain (ROB) were examined with saturation binding experiments. The regional distribution of [3H]-R-alpha-methylhistamine binding sites in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…4 In addition, there is a moderate increase in the release of histamine from the anterior hypothalamus of PCA rats. 5 Finally, significantly increased levels of histamine have been found in the cerebrospinal fluid of patients with HE. 3 Taken together, these findings point to an increased availability of histamine in the brain of rats with PCA and patients with HE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In addition, there is a moderate increase in the release of histamine from the anterior hypothalamus of PCA rats. 5 Finally, significantly increased levels of histamine have been found in the cerebrospinal fluid of patients with HE. 3 Taken together, these findings point to an increased availability of histamine in the brain of rats with PCA and patients with HE.…”
Section: Discussionmentioning
confidence: 99%
“…Among the least exploited consequences of HE are the marked changes in the brain histaminergic system, which have been previously documented both in patients with HE 3 and in rats with portacaval anastomosis (PCA), a well-established animal model of the disease. [4][5][6][7][8] There is substantial evidence that histamine acts as a neurotransmitter in mammalian brain. 9 Histaminergic neurons are located exclusively in the tuberomammillary nucleus of the posterior hypothalamus and send their varicose fibers to almost every region of the brain.…”
mentioning
confidence: 99%
“…12,17 Furthermore, the spontaneous, as well as the depolarizationinduced and pharmacologically induced histamine release from anterior hypothalamus are significantly increased in these rats. 17 Histamine, through the activation of postsynaptic H 1 receptors, is involved in the regulation of the mechanisms of arousal, 19,20 locomotor activity, 21-24 feeding behavior, and energy balance, 25,26 and circadian rhythmicity (for reviews, see Tuomisto 27 and Nowak 28 ). We have previously suggested that histaminergic synaptic imbalance may have contributed to the sleep disturbances in rats with PCA.…”
mentioning
confidence: 99%
“…We have previously suggested that histaminergic synaptic imbalance may have contributed to the sleep disturbances in rats with PCA. 18 We have now examined the effects of histamine H 1 receptor blockade on feeding, locomotor activity, and circadian rhythmicity in rats with long-term PCA to find out whether the modified histaminergic neurotransmission in the brain of rats with portacaval anastomosis 6 months after surgery 12,[16][17][18] has also participated in the generation and maintenance of the disturbances in the circadian rhythmicity of feeding and locomotor activity. Pyrilamine (mepyramine), a selective and high-affinity H 1 receptor antagonist, 29 was used to block histamine H 1 receptors in the CNS.…”
mentioning
confidence: 99%
See 1 more Smart Citation